Replacement Therapies in Metabolic Disease - Keller, Alexander S.; Keller IV, T.C. S.; DeLalio, Leon J.; Shahab, Guleer; Yang, Yang; Murphy, Sara A.; Shu, Xiaohong; Isakson, Brant E. (Current Pharmaceutical Biotechnology, 2018)
Background: Replacement therapies have revolutionized treatment paradigms in metabolic diseases by restoring defective enzymes and supplementing missing downstream metabolites. Through most of the 20th century, no targeted therapies existed for these conditions, the only treatment options available focusing on symptoms rather than the underlying disorders. Improved understanding of the molecular pathways underlying metabolic disease has allowed not only supplementation of missing metabolites and reduction of upstream substrates, but replacement of defective or missing enzymes. Objective: Modern genetic technologies have facilitated steady progress in recombinant enzyme innovation, providing treatments that replicate not only endogenous enzymes, but also their posttranslational modifications to optimize their delivery and function. The advent of the gene therapy revolution brings a possibility of new therapeutic opportunities in which the enzymes at the core of metabolic diseases may not only be added back, but genetically replaced. Conclusion: With the next generation of treatments approaching, this review examines the recent decades of replacement therapy innovation in metabolic disease and discusses the challenges and opportunities for the next generation of treatments.
Keywords: gene therapy